Customized Titanium Mesh for Repairing Cranial Defects: A Method With Comprehensive Evaluation. Issue 8 (November 2015) - Zhang, Jingjing; Long, Jianhong; Yang, Xinghua; Lei, Shaorong; Xiao, Muzhang; Fan, Pengju; Qi, Min; Tan, Wuyuan
Abstract : Abstract: Titanium cranioplasty is one of the well-established and widely used techniques for repairing cranial defects. In this paper, we present an improved way to design and create titanium meshes with more evaluation process. Computed tomography scan data of patients were used to create three-dimensional virtual models. Implants were designed with NX ImageWare 13.2 (Siemens PLM Software, Plano, TX).1 Final titanium meshes were assessed by Geomagic Studio 12 (Geomagic, Inc., Morrisville, NC)2 and NX ImageWare 13.2.1 Titanium meshes were designed and applied to cranioplasty surgery on 8 patients. Postoperative results were evaluated by computed tomography scanning and further analyzed with rainbow difference tomography. All patients were satisfied with the outcome. With this method, surgeons, engineers, and patients work together to evaluate and edit implant design. Our method provides better communication and comprehensive evaluation, which result in a satisfying outcome.